Click Chemistry-Based Synthesis of New 1-formyl-naphthalen-2-yloxymethyl-1, 2, 3-triazoles, Anticancer Screening and 2D-NMR Studies. Issue 6 (2nd November 2021) - Dhuda, Gautam Kumar; Kapadiya, Khushal; Ladva, Paresh; Jivani, Amita; Modha, Jayesh
Abstract: A series of 10 various 2-[5-(1-formyl-naphthalen-2-yloxymethyl)-[1, 2, 3]triazole-1-yl]-substituted phenyl acetamides (5a-5j) were synthesized through copper(I)-catalyzed 1, 3-dipolar cycloaddition reaction of 2-(prop-2-ynyloxy)naphthalene-1-carbaldehyde (2) and different 2-azido- N -phenylacetamide derivatives (4) under the assorted click chemistry pathway. Its specific biocompatibility to solidify more effectual lead discovery procedures in medicinal chemistry has its own space in the anticancer drugs discovery module. The structural compatibility was studied by HMBC and APT type of NMR techniques. In vitro, the anticytotoxic evaluation indicated that some of the synthesized molecules exhibited potent inhibitory activities in various cancer cell lines. It has been found that out of 10 screened molecules, 5a and 5h demonstrated good cytotoxic potential against CNS, Melanoma, and Breast cancer panel. Derivatives 5e and 5i, bearing 4-fluoro and 4-bromo groups, respectively, demonstrated average cytotoxic potential against CNS, Ovarian, and Renal cancer. GRAPHICAL ABSTRACT: UF0001